Effect of Tm2O3 addition on the physical, structural, elastic, and radiation-resisting attributes of tellurite-based glasses - Bassam, S.A.; Naseer, K.A.; Prakash, Anagha J.; Mahmoud, K. A.; SuchandSangeeth, C.S.; Sayyed, M. I.; Alqahtani, Mohammed S.; Sheikh, E. El; Khandaker, Mayeen Uddin * (Elsevier, 2023)
The influence of adding Tm2O3 in the tellurite-based glasses is analyzed through their physical, optical, structural, elastic, and gamma rays resisting features. The proposed glasses are prepared via the classic melt-quenching technique. As the Tm2O3 concentration is raised (TeO2 reduced), glass properties like density (ρ), and refractive index (nd) are elevated indicating an enhancement in the glass structure. Elastic constants were analyzed to rise with Tm3+ addition due to the production of bridging oxygens in the system. The elastic constants E, K, and G were perceived to rise with the Tm3+ concentration from 90.4 to 157 GPa, 131−156 GPa, 38.7−42.1 GPa. The μ values reduced from 244.14 t0 0.19 cm−1 (for the TmZT1 sample) and from 298.82 to 0.23 cm−1 (for TmZT5) when the γ-ray energy enriched between 0.015 and 15 MeV. And there is a good agreement between the MC simulated μm values and the theoretically calculated XCOM μm values. The difference (%) between both of the mentioned results is found in the range of ±2%. At γ ray energy of 0.662 MeV, as glass thickness increases, the radiation protection efficiency of each sample increases from 17.5 to 68.6% (for TmZT1), from 33.2 to 70.2% (for TmZT2), from 34.2 to 71.5% (for TmZT3), from 35.3 to 72.9% (for TmZT4), and from 36.4 to 74.3% (for TmZT5).